Human expert finding for web-based Mathematics question-answering system - Khoestadi, Gabriella. (2011)
Question Answering (QA) community such as Yahoo! Answers [1] is purposely built to be a communication portal between people who are having questions and other parties who possess the expertise to answer those posted questions. To narrow down the universe of question types, specific QA communities are built especially for educational domain such as mathematics. Mathematical QA communities should allow users to search, ask, answer, and discover mathematical questions. However, at times, there will not be any available answer in the database for the inputted question query.